PEMODELAN SLIDING MODE CONTROL UNTUK REGULASI TEGANGAN KELUARAN DC-DC ISOLATED FULL BRIDGE CONVERTER - Muhammad Akbar Amran; Mochammad Rusli; Waru Djuriatno (Jurnal Mahasiswa TEUB, 2023)
Technological developments in electronic components and circuits are capable of producing a direct current (DC) power supply system, which is produced by converting the input DC voltage to a higher or lower output DC voltage. To enhance energy conversion efficiency, precise and responsive control is essential. One widely used approach is to employ a DC-DC full bridge converter topology. The objective of this study is to model a Sliding Mode Control (SMC) to regulated the output voltage of a DC-DC full bridge converter. The research involves designing and simulating the converter circuit subsystem, controller design, and specifying the equipment to closely resemble the in real conditions. Through experimentations, it is observed that the designed controller meets the expected specifications allowing the converter to simulate stable output voltage regulation. The SMC methods is chosen for its adaptive and nonlinear nature, enabling it to produce a constant output voltage even when the input voltage from the DC source varies. The input DC voltage specification is 24 V, while the output voltage generates 48 V. MATLAB/Simulink is employed for simulation to design the entire system and present the research result in graphical form. Keyword: Fuel Cell, DC-DC Full Bridge Converter, Sliding Mode Control, Voltage Regulation.